Outsiders looking in? Challenging reading through creative practice - Abegglen, Sandra; Burns, Tom; Middlebrook, David; Sinfield, Sandra (Journal of University Teaching and Learning Practice, 2020)
Becoming well read, especially in academia, is key to being part of the university - and of society. Academic reading is ‘tricky business’ especially for those widening participation students not necessarily familiar with the forms and processes of Higher Education. To foster these students’ academic literacies and practice, rather than the decontextualised teaching of ‘skills’, we create empowering social spaces for authentic collaborative reading. To facilitate this, we present text ‘differently’: text as scroll. A textscroll can be made by taping article or chapter pages together, side-by-side. Textscrolls open up the contested bookspace and make the written word accessible. They foster dialogic and multimodal interaction with texts and, if woven into a developmental embodied sequence of learning activities, help develop an understanding of academic reading as a wider social practice. Student and staff feedback show that scrolls are liberating. Scrolls, in embodied ways, make university reading meaningful and can authentically scaffold entry into epistemic communities. Scrolls help learners access the written word - and enjoy reading.